2005
DOI: 10.1016/j.biopsych.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Treatment in Activity-Based Anorexia

Abstract: Background: Activity-based anorexia (ABA) is considered an animal model of anorexia nervosa (AN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 42 publications
1
65
0
2
Order By: Relevance
“…Previously, we observed that physical activity per se does not result in up-regulation of POMC gene expression (Hillebrand et al, 2005c;. One may argue that circadian fluctuation of POMC mRNA expression can also play a role in up-regulation of POMC.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, we observed that physical activity per se does not result in up-regulation of POMC gene expression (Hillebrand et al, 2005c;. One may argue that circadian fluctuation of POMC mRNA expression can also play a role in up-regulation of POMC.…”
Section: Discussionmentioning
confidence: 80%
“…Conversely, leptin administration decreases wheel running in rats (Hillebrand et al 2005). Gelegen et al (2007) compared the C57BL/6J and DBA/2J strains of inbred mice, which display low and high levels of anxiety and activity-related behaviors, respectively, in the activity/stress model.…”
Section: Animal Models Of Anmentioning
confidence: 98%
“…This key role of leptin in SIH has recently been confirmed in an independent study. 104 Accordingly, hypoleptinaemia can trigger a strong behavioural response, which can be corrected via increments of circulating leptin levels.…”
Section: Hyperactivitymentioning
confidence: 99%
“…107 Nevertheless, it has been suggested that a hyperactive melanocortinergic system underlies the SIH phenotype. 104,105,107 Other possible effectors downstream of the leptin receptor that might be implicated in SIH are the serotonergic and/or dopaminergic system as well as the hypothalamic-pituitary adrenal axis.…”
Section: Hyperactivitymentioning
confidence: 99%